India’s Policies in Support of the New Space - I. V. Danilin; E. P. Shavlay (Vestnik MGIMO-Universiteta)
Just like in the Cold War, space has re-emerged as an arena of international rivalry. However, this time, the space industry sees new actors partaking in the race to the top, as the competition is not just between states; commercial players are increasingly taking the field. The latter is not limited to established large companies but includes small and medium-sized innovative enterprises, forming the so-called New Space. Among the countries facing such a multifaceted challenge is India, whose space industry is pursuing a catch-up strategy in many respects and has only recently stepped up the growth of the commercial space segment.Considering the key importance of the public support for this segment, the article discusses the main trends, factors, and specifics of the Indian New Space policy. We use comparative analysis to assess the current state and prospects of the industry and its possible implications for the Indian global positions.The study shows that New Delhi aims to embrace new realities amidst ambitious economic targets, social challenges, and growing geopolitical tensions with China, with the pandemic acting as a catalyst. Thanks to innovative measures, India has already become one of the central space players, but it still falls short of leadership in the New Space due to its resourceconstrained and state-centered course. Nevertheless, although its New Space is still at its infant stage, the future looks promising. However, the success of the Indian astropreneurs will also depend on the rise of efficiency of the national policies – a process likely to happen due to internal and global challenges.